An investigation of the effect of high temperature on the strength compression and ultrasonic pulse velocity of self-compacting concrete - Hadji Ben Salah; Mostefa Hani (The Journal of Engineering and Exact Sciences)
One of the most significant mechanisms of deterioration in self-compacting concrete (SCC) structures over the course of their service life is exposure to elevated temperatures. For this reason, the effects of elevated temperatures on the residual mechanical properties of SCC made of various cementitious additions (silica fume (SF), limestone filler (LF), and crushed dune sand (SD)) was investigated via partially substituting amount of Portland cement in the SCC. The SCC was formed and heated with the coupling procedure of heating-cooling at ambient temperatures ranging from 20, 150, 400, 600, and 800 °C. The compressive strength (CS) and ultrasonic pulse velocity (UPV) were measured after cooling at room temperature of 20 °C. The findings show that CS and UPV exhibit intriguing outcomes for all self-compacting concretes. Otherwise, the UPV decreases with temperature in the range of 250 and 800 °C. In addition, at 600 °C, SCC-SF and SCC-SD have the highest residual compressive strengths, 31.20 and 23.80 MPa, respectively.